2016
DOI: 10.1111/edt.12298
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone App as an aid in the emergency management of avulsed teeth

Abstract: The Dental Trauma App alone is an effective means of providing accessible knowledge to guide laypeople in managing tooth avulsion, and it can be superior to a lecture-based delivery of information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 29 publications
2
53
0
3
Order By: Relevance
“…In this study, the greater accuracy observed with the mobile app compared to the print format could be attributed to several factors. Active learning is defined as an instructional method that engages students in the learning process . Studies have proven its positive impact over more traditional ways of delivering information such as through textbooks or lectures in educational settings .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the greater accuracy observed with the mobile app compared to the print format could be attributed to several factors. Active learning is defined as an instructional method that engages students in the learning process . Studies have proven its positive impact over more traditional ways of delivering information such as through textbooks or lectures in educational settings .…”
Section: Discussionmentioning
confidence: 99%
“…Active learning is defined as an instructional method that engages students in the learning process. 28 Studies have proven its positive impact over more traditional ways of delivering information such as through textbooks or lectures in educational settings. 29 The interactive step-by-step guide of the mobile app may be less complex and more likely to actively engage users thereby enhancing information acquisition and retention compared to traditional resources.…”
Section: Ta B L E 4 Cdst Survey Responsesmentioning
confidence: 99%
“…It is designed to provide parents, teachers, sport coaches, and others with effective first aid training in case of dental trauma. A recent study showed that the dental trauma app alone is an effective tool for providing knowledge to guide the public in managing dental avulsion, and it can be superior to the other educational interventions used [22]. Therefore, disseminating information on the emergency management of dental avulsion using the dental trauma app would be a valuable educational tool for parents, especially due to the immediate availability of such a tool at the place of injury.…”
Section: Discussionmentioning
confidence: 99%
“…The increased amount of dental morbidity and tooth loss are due to trauma to the dentition. Untreated injured teeth can affect psychological, physical and emotional status of the child and appropriate treatment plays a vital role in preserving the health of such traumatised teeth. Initial management that is provided at the time of injury is a critical factor in predicting the long‐term prognosis.…”
Section: Introductionmentioning
confidence: 99%